2013
DOI: 10.1371/journal.pone.0049231
|View full text |Cite
|
Sign up to set email alerts
|

Neural Basis of Scientific Innovation Induced by Heuristic Prototype

Abstract: A number of major inventions in history have been based on bionic imitation. Heuristics, by applying biological systems to the creation of artificial devices and machines, might be one of the most critical processes in scientific innovation. In particular, prototype heuristics propositions that innovation may engage automatic activation of a prototype such as a biological system to form novel associations between a prototype's function and problem-solving. We speculated that the cortical dissociation between t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2013
2013
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(9 citation statements)
references
References 31 publications
(40 reference statements)
0
9
0
Order By: Relevance
“…However, this region has received scant attention in past research. As increased activity in the lingual gyrus has been observed using an insight task with heuristic prototypes, it has been suggested that it might be involved in forming novel associations using heuristic information (Luo et al, 2013).…”
Section: Neural Network Involved In Insight Processingmentioning
confidence: 99%
“…However, this region has received scant attention in past research. As increased activity in the lingual gyrus has been observed using an insight task with heuristic prototypes, it has been suggested that it might be involved in forming novel associations using heuristic information (Luo et al, 2013).…”
Section: Neural Network Involved In Insight Processingmentioning
confidence: 99%
“…As noted earlier, Archimedes realized the relationship between the volume of an irregularly shaped object and the volume of water it displaced. This is an example of heuristic prototyping where the problem-solver notices an event in the environment, which then triggers the automatic activation of a heuristic prototype and the formation of novel associations (between the function of the prototype and the problem) which they can then use to solve the problem (Luo et al, 2013 ). Although still in its relative infancy, there has been some recent research into the neural basis for heuristic prototyping.…”
Section: Role Of the Environmentmentioning
confidence: 99%
“…Scientific findings [ 1 3 ] have suggested a two-fold structure of the cognitive processes that includes heuristic and explicit components. By using the heuristic thinking mode, people automatically process information that tends to be invariant across days [ 2 ].…”
Section: Introductionmentioning
confidence: 99%
“…This mode allows an individual to behave according to a conventional habit, which includes the typical practical and mental actions of everyday work [ 4 ]. In contrast, the explicit thinking mode supports an individual’s creativity by changing existing mental models and building new ones [ 3 ]. There appears to be a tradeoff between the tendency to employ a previously learned heuristic mode and the ability to adopt an explicit mode [ 1 , 5 ].…”
Section: Introductionmentioning
confidence: 99%